Determination of Vibrational Population Distribution for the N2+ (1N) Ion Band System from Spacelab 1 - Jong Won Eun (Journal of Astronomy and Space Sciences, 1989)
The Spacelab 1 data represented the first multiband spectral measurements of the N2+ first negative ion bands system in the thermospheric dayglow, and the first opportunity to make a detailed comparison of the vibrational and rotational distributions over bands out to v'=5. The main purpose of this study was to deduce the excitation processes of N2+(1N) bands by determining vibrational population distributions for the upper states of N2+(1N). The vibrational population distributions to achieve a best fit to the measured Spacelab 1 data were summarized and also compared with those theoretically derived.